2021
DOI: 10.3389/fphar.2021.708093
|View full text |Cite
|
Sign up to set email alerts
|

Combining Sodium Butyrate With Cisplatin Increases the Apoptosis of Gastric Cancer In Vivo and In Vitro via the Mitochondrial Apoptosis Pathway

Abstract: Introduction: The gastrointestinal malignancy, gastric cancer (GC), has a high incidence worldwide. Cisplatin is a traditional chemotherapeutic drug that is generally applied to treat cancer; however, drug tolerance affects its efficacy. Sodium butyrate is an intestinal flora derivative that has general anti-cancer effects in vitro and in vivo via pro-apoptosis effects and can improve prognosis in combination with traditional chemotherapy drugs. The present study aimed to assess the effect of sodium butyrate c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…Furthermore, treating pancreatic carcinoma cell lines with sodium butyrate increases cell sensitivity to SN-38, cisplatin, and fluorouracil chemotherapies by inducing histone acetylation and p53 expression and subsequently increasing apoptosis [ 58 ]. A similar synergic effect was also observed after combined butyrate treatment with docetaxel, irinotecan, gemcitabine, or cisplatin both in vitro and in vivo against various types of tumors [ 45 , 46 , 47 , 59 ]. The co-administration of docetaxel and butyrate enhanced docetaxel response by upregulation and downregulation of apoptosis and proliferation-related proteins, respectively, [ 59 ].…”
Section: Scfas and Cancer Treatment Responsementioning
confidence: 54%
See 1 more Smart Citation
“…Furthermore, treating pancreatic carcinoma cell lines with sodium butyrate increases cell sensitivity to SN-38, cisplatin, and fluorouracil chemotherapies by inducing histone acetylation and p53 expression and subsequently increasing apoptosis [ 58 ]. A similar synergic effect was also observed after combined butyrate treatment with docetaxel, irinotecan, gemcitabine, or cisplatin both in vitro and in vivo against various types of tumors [ 45 , 46 , 47 , 59 ]. The co-administration of docetaxel and butyrate enhanced docetaxel response by upregulation and downregulation of apoptosis and proliferation-related proteins, respectively, [ 59 ].…”
Section: Scfas and Cancer Treatment Responsementioning
confidence: 54%
“…Combined gemcitabine and butyrate treatment also further prompted apoptosis and reduced tumor-associated stromatogenesis in pancreatic ductal adenocarcinoma models [ 46 ]. Additionally, butyrate enhanced tumor apoptosis and the suppression of tumor growth, migration, and invasion capacity of gastric cancer cell lines treated with cisplatin [ 47 ] ( Figure 2 ). Similar to butyrate, it has been demonstrated that propionate enhances the anti-tumor activity of cisplatin against human hepatocellular carcinoma cells.…”
Section: Scfas and Cancer Treatment Responsementioning
confidence: 99%
“…It was further confirmed by Engelhardt et al [ 26 ] in studies using an in vivo GBM rat model. Moreover, several studies showed that combined treatment with butyrate and already available drugs (such as docetaxel or cisplatin) significantly improved their therapeutic effects [ 27 , 28 , 29 ]. Our research confirmed that targeting cell metabolism and epigenetic modifications is a powerful anti-cancer strategy.…”
Section: Discussionmentioning
confidence: 99%
“…The detection of cell apoptosis affected by cratoxylumxanthone C was accomplished by flow cytometry ( Li et al, 2021a ; Zhang et al, 2021a ). Briefly, A549 cells were harvested and seeded in 12-well plates (1 × 10 5 cells per well) and incubated for 24 h at 37°C.…”
Section: Methodsmentioning
confidence: 99%